-6y+2=4-6y

Simple and best practice solution for -6y+2=4-6y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6y+2=4-6y equation:


Simplifying
-6y + 2 = 4 + -6y

Reorder the terms:
2 + -6y = 4 + -6y

Add '6y' to each side of the equation.
2 + -6y + 6y = 4 + -6y + 6y

Combine like terms: -6y + 6y = 0
2 + 0 = 4 + -6y + 6y
2 = 4 + -6y + 6y

Combine like terms: -6y + 6y = 0
2 = 4 + 0
2 = 4

Solving
2 = 4

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| f(x)=5x^2-6x+5 | | A=pir^2+2pirh | | X^4-40X^2-33=0 | | 4(3n+1)=6(2n-1) | | 9j=-7+10j | | 24.3=12.4+2a | | -3x-2+1=-7 | | -7g=-2-6g | | 12x^2-16x-6=0 | | -7g=-2-6 | | 12k=-36 | | 16-20x-21-6x=18-6x-12x-1 | | -5y+10=-6y | | 23a+7= | | 9v=10v+9 | | 17-6x+3x-5=x+11+4x | | -3m+10=-4m | | 17-6x+3x-5=x+11 | | 6+16x=17x+2 | | 5h=7h+8 | | 24.3=14.4+2a | | 18a-7= | | 6=-5d+11 | | 10x-14-6x=18 | | 2(2x+5)=4 | | 4z-4=10 | | 9x+16=6x+106 | | 10p^2-90p=0 | | x-75x=6x | | 0.5x+0.3=1.2 | | 5(12-x)=25 | | 2x(8x-5)=(5-4x)2 |

Equations solver categories